PENEGAKAN HUKUM TERHADAP PELANGGARAN PRINSIP KEHATI-HATIAN DALAM PEMBERIAN KREDIT PERBANKAN - Khalimi, Khalimi; Alam, Kodrat (Yustitia, 2022)
Banks have a strategic function in the economy in every country. In this strategic function, banks are always faced with regulations in every step of their business. The regulation is not only on how to establish or permit to establish a bank, but each bank balance sheet is regulated in such a way that the bank is in a healthy level that is maintained in order to guide the principles or principles of banking. One of the banking principles that has become a serious concern for law enforcers is the principle of prudence. We can see the factual implementation of the precautionary principle in the application of in-depth credit analysis using the five c principle, which includes elements of character (character), capital (capital), capacity (customer's ability), condition of economy (economic condition), and colleteral (collateral). The principle of prudence is very necessary, especially in the case of banks wishing to channel funds to the public in the form of credit or financing. The precautionary principle is often interpreted as a principle that banks in carrying out their business must pay attention to various risks, both administrative risks and legal risks. The meaning of prudence is very broad to be interpreted, so that any violation of risk is categorized as a violation of the precautionary principle. Violation of the precautionary principle has become a law enforcement tool to ensnare banking managers, especially in providing credit as a crime. There needs to be a banking regulatory product that specifically regulates the limitations of any sanctions that are referred to as administrative violators or criminal acts of prudential principles. Because, if it is not regulated clearly and firmly, it will create legal uncertainty